Selective syntheses of vinylenedithiathiophenes (VDTTs) and dithieno [2,3-b;2 ',3 '-d]thiophenes (DTTs); building blocks for pi-conjugated systems - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Selective syntheses of 3,4-vinylenedithiathiophenes (VDTTs) and dithieno[2,3-b:2',3'-d]thiophenes (DTTs), having Ph, 4-CH3OC6H4, 4-BrC6H4, 4-NO2C6H4 and 4-(CH3)(2)NC6H4 groups, were achieved through the reaction of 1,8-diketone with phosphorus decasulfide (P4S10). The reaction could be shifted between VDTT and DTT by adding base (sodium bicarbonate) or acid (para-toluenesulfonic acid), respectively, to the reaction mixture. While the VDTTs were obtained in moderate yields, an important achievement has been made with the syntheses of the DTTs, obtaining them in higher yields compared with the previous report. Polymers of the VDTTs, which are the analogues of ethylenedioxythiophene, EDOT, were prepared using FeCl3. Unfortunately, all attempts for their electropolymerization failed. Spin density calculations revealed that none of the VDTTs had a significant positive spin density at the 'alpha' carbon atoms of the thiophene ring. Considering their solubility and functional groups, which could be further derivatized, they are useful building blocks for the preparation of new organic materials. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Vinylenedithiathiophene; Dithienothiophene; Phosphorus decasulfide (P4S10); Ethylenedioxythiophene; 3,4-ETHYLENEDIOXYTHIOPHENE EDOT; TETRATHIAFULVALENE DERIVATIVES; LAWESSONS REAGENT; POLYMERS; CRYSTAL; 1,4-DITHIINS; PRECURSORS